Penerapan Model Pembelajaran Kooperatif Tipe STAD Berbantuan Media Flip Chart Dilengkapi LKS Tebak Gambar Untuk Meningkatkan Hasil Belajar Siswa : (Implementation of The STAD Type Cooperative Learning Model Using Flip Chart Media Completed With The Picture Guessing LKS to Improve The Learning Outcomes of Grade) - Ambu, Soviati Ata; Bano, Vidriana Oktoviana; Tamaela, Kevin Andrean (BIODIK, 2026)
This research is motivated by the low learning outcomes and activities of grade XII-IPA students at SMA Muhammadiyah Waingapu on Biotechnology material. The main problems include low literacy, lack of focus, and learning methods that are not yet varied. This Classroom Action Research (CAR) aims to improve cognitive and affective learning outcomes through the Student Teams Achievement Division (STAD) cooperative model assisted by Flip chart media and LKS Tebak Gambar (Guess the Picture) worksheets. The research subjects consisted of 26 students. Data were collected through tests (post-test), observation, and documentation, then analyzed quantitatively descriptively. The results showed a significant increase in each cycle. The average cognitive score increased from 59.61 (Pre-cycle) to 74.23 (Cycle I), and reached 86.15 (Cycle II) with a classical completeness of 88%. The affective aspect also increased, marked by the dominance of the "Good" and "Very Good" categories in Cycle II. It was concluded that the application of the STAD model assisted by Flip Chart media and LKS Tebak Gambar was effective in improving student learning outcomes and creating a more interactive and enjoyable learning atmosphere. Abstrak. Penelitian ini dilatarbelakangi oleh rendahnya hasil belajar dan aktivitas siswa kelas XII-IPA SMA Muhammadiyah Waingapu pada materi Bioteknologi. Masalah utama meliputi rendahnya literasi, kurangnya fokus, dan metode pembelajaran yang belum variatif. Penelitian Tindakan Kelas (PTK) ini bertujuan meningkatkan hasil belajar kognitif dan afektif melalui model kooperatif tipe Student Teams Achievement Division (STAD) berbantuan media Flip chart dan LKS Tebak Gambar. Subjek penelitian terdiri dari 26 siswa. Data dikumpulkan melalui tes (post-test), observasi, dan dokumentasi, kemudian dianalisis secara kuantitatif deskriptif. Hasil penelitian menunjukkan peningkatan signifikan pada setiap siklus. Rata-rata nilai kognitif meningkat dari 59,61 (Pra-siklus) menjadi 74,23 (Siklus I), dan mencapai 86,15 (Siklus II) dengan ketuntasan klasikal 88%. Aspek afektif juga meningkat, ditandai dengan dominasi kategori "Baik" dan "Sangat Baik" pada Siklus II. Disimpulkan bahwa penerapan model STAD berbantuan media Flip chart dan LKS Tebak Gambar efektif meningkatkan hasil belajar siswa dan menciptakan suasana pembelajaran yang lebih interaktif serta menyenangkan.